Comparative Legal Analysis of the Council Directive 91/533/EEC on an Employer’s Obligation to Inform Employees of the Conditions Applicable to the Contract or Employment Relationship with the Current Labor Law of All Its Member States - Bozhko, Volodymyr; Zadorozhnyy, Volodymyr; Kulchii, Inna; Smahliuk, Victoria (International Journal of Engineering and Technology, 2018)
The European Commission seeks to ensure that the EU labour market under the influence of innovations, digital technologies, on the one hand, ensures effective protection of the rights of all employees, creates conditions for a better life and work in the EU, and on the other hand, has increased the competitiveness of the EU by increasing the profitability of employers in the long run. To this end, in the European Union on 14.10.1991, Council Directive 91/533/EEC on the obligation of the employer to inform employees of the conditions applicable to the employment contract or employment relationship.The same article is devoted to the comparative legal study of the applicable labour laws of individual member countries of the European Union and Ukraine with the said Directive.In addition to the above, much of the attention in the article is focused on the analysis of the draft European Parliament and Council Directive on â€˜Transparent and predictable working conditions in the European Unionâ€™Â [1], approved by the European Commission on 21 December, 2017, which is planned to be adopted instead of the applicable Council Directive 91/533/EEC.Â Â